2000
DOI: 10.1093/ndt/15.4.502
|View full text |Cite
|
Sign up to set email alerts
|

B lymphopenia in uraemia is related to an accelerated in vitro apoptosis and dysregulation of Bcl-2

Abstract: Our data indicate that B lymphopenia in CRF may be partially attributed to an increased susceptibility to cell death by apoptosis that is associated with a decreased expression of Bcl-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 35 publications
12
103
0
10
Order By: Relevance
“…It has been suggested that one of the major causes of this disturbance is an increased susceptibility to the death of B cells by apoptosis (48). However, it has been documented that Ig levels, serum IgG isotypes, and both IgM and IgA production are normal in dialysis patients (44).…”
Section: Alterations Of Adaptive Immune Systemmentioning
confidence: 99%
“…It has been suggested that one of the major causes of this disturbance is an increased susceptibility to the death of B cells by apoptosis (48). However, it has been documented that Ig levels, serum IgG isotypes, and both IgM and IgA production are normal in dialysis patients (44).…”
Section: Alterations Of Adaptive Immune Systemmentioning
confidence: 99%
“…Reports from human medicine discussing the number of neutrophils are controversial. They found a decreased number of neutrophils (Nairn et al, 2005), unchanged neutrophil counts (AlvarezLara et al, 2004) and an increased number of neutrophils in comparison with the healthy control (Fernandez-Fresnedo et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…According to reports from human medicine, lymphopoenia may result from higher apoptosis of these cells, but the proper mechanisms are still unclear (Fernandez-Fresnedo et al, 2000;Jaber et al, 2001). In dogs with CRF and clinical symptoms we observed a statistically highly significant reduction of eosinophils in comparison with the healthy control.…”
Section: Discussionmentioning
confidence: 99%
“…Співвідношення Т4/Т8 перебували в межах нор-мального діапазону [5]. Деякі дослідження по-казують порушену функцію нейтрофілів, змен-шення числа лімфоцитів, помірне зниження CD3 Т-лімфоцитів, зниження відношення CD4 до CD8 і зменшення числа В-лімфоцитів [6,7]. У пацієнтів із тривалою ХНН лімфопенія може бути обумовлена зниженою проліферацією клітин [8] чи прискоренням апоптозу Т-і В-лімфоцитів [6].…”
Section: особливості стану імунної системи в потенційних реципієнтів unclassified